Analysis of lime mixture on the characteristics of the physical and mechanical properties of the soft soil - Hendri Tri Saputra; Agus Tugas Sudjianto; Aji Suraji; Cakrawala Cakrawala (CV. Creative Tugu Pena, 2025)
The object of this study is Lanau Landu Land from the Kedung Baruk region, East Surabaya. This type of soil is known to have unfavorable geotechnical characteristics, such as low carrying capacity, high water content, and a large level of saturation. This study aims to analyze the effect of mixture of calcite lime on changes in physical and mechanical properties of soft sauce soil. Calcite lime used has a high level of CaCo₃ and mixed into the soil with variations of 0%, 5%, 10%, 15%, and 20%. Laboratory testing is carried out including water content, specific gravity, Atterberg limit, maximum dry weight weight, and free compressive strength. The results showed that the addition of calcite lime was able to reduce water content and soil plasticity, as well as increasing the density and free compressive strength, especially at 10%levels. However, at 20%levels, there was a decrease in density due to the formation of lime aggregates that were not homogeneous. Chemically, the reaction between calcium carbonate and silica/alumina from the soil forms calcium silicate hydrate compounds (CSH) and calcium aluminate hydrate (CAH), which increases bonds between soil particles. This process improves the micro -soil structure, increases its strength and stability. Capur calcite also provides alternative stabilization that is more economical and environmentally friendly than cement or flying ash, even though the reaction is slower. Thus, chalk calcite is effective in improving the quality of Lanau Soft soil in Kedung Baruk, East Surabaya.